Gender aspects of empathy in online learning of adolescents - Pidbutska, N. V.; Demidova, Yu. Ye.; Knysh, A. Ye. (Foundation Pro Scientia Publica, Poland, 2020)
During the study, the aim has been achieved and all the objectives have been fulfilled, in particular: 1) “involvement in online learning” and "quality of online learning" are defined as criteria for online learning successful performance; 2) expert assessment of the study results is carried out, allowing us to determine that female participants show mainly medium and high levels of online learning performance, while male participants show low and medium-level results; 3) it is determined that the correlation between the level of performance of online learning and empathy in the group of girls is higher than in the group of boys.
Keywords: online learning; empathy; academic performance; adolescents; distance learning; education